Deformation and fracture characteristics of Al6092/SiC/17.5p metal matrix composite sheets due to heat treatments - Gatea, Shakir; Ou, Hengan; McCartney, Graham (Elsevier, 2018)
In metal matrix composite (MMC) materials, the reaction between the metal matrix and reinforcement particles could change the composition of the matrix and the interface and lead to interfacial compounds. These intermetallic compounds may have either a deleterious effect to the mechanical properties or beneficial effect in enhancing the toughness and ductility of the composite. An aluminium 6092 alloy with 17.5% volume fraction silicon carbide (SiC) particles sheet manufactured by means of powder metallurgical method, heat treated to T6 condition, is used to obtain a fundamental understanding of the heat treatment effect on the fracture mechanism, the microstructural changes and the interface between the Al-matrix and SiC particles. Changes in the microstructure of the Al/SiCp and the topography of the fracture are investigated using scanning electron microscopy (SEM) coupled with energy dispersive X-ray spectroscopy (EDS) and transmission electron microscopy (TEM) to characterize the precipitate and intermetallic compounds formed at the Al/Sic interface. X-ray diffraction (XRD) is utilized to characterize the phase formation and to give confidence in the results of TEM and EDS. Tensile tests with different strain rates (8 × 10−5, 8 × 10−4, 8 × 10−3, 8 × 10−2 and 0.16 s−1) were carried out to study the toughness and to find a correlation between the strain rate and heat treatment. Under T6 condition, the results show that the mechanical property of this MMC is less ductile due to the formation of precipitations as a result of either the interaction between the Al and SiCp or from hardening precipitation treatment, e.g. Al2Cu, Al4Cu2Mg8Si7 and MgAl2. O-condition annealing can reduce the detrimental effect of the intermetallic compounds in the interface region and improve the toughness and ductility of the material by decreasing the intermetallic compound (Al2Cu). However, the Al/SiC sheet treated with O-condition annealing is more sensitive to the strain rate than the one treated with T6.